Fiqh al-Bī’ah and Sustainable Waste Governance: A Synthesis between Islamic Ethics and Sustainable Waste Management - Sugeng Riyadi; Syufaat; Suratman (Immortalis Journal of Interdisciplinary Studies, 2026)
Rapid economic growth and urbanization have increased global waste production, underscoring the need for sustainable waste governance. In Indonesia, Law No. 18 of 2008 on Waste Management mandates the principles of responsibility, sustainability, and justice in waste management; however, its implementation continues to face challenges, including low public awareness and a weak recycling system. On the other hand, fiqh al-bī’ah (Islamic environmental jurisprudence) offers an ethical framework that emphasizes cosmic balance, avoidance of wastefulness, and the human mandate as khalifah (steward) on Earth. This article examines the synthesis of the principles of fiqh al-bī’ah with the framework of sustainable waste governance to develop a waste management model aligned with Islamic ethics. The research employs a descriptive qualitative approach, including a literature review, analysis of regulatory documents, and field studies in Banyumas Regency, which serves as the case study. The findings show that the principles of fiqh al-bī’ah, such as the protection of life and soul, the balance of production and consumption, and the maintenance of ecosystem balance, align with the hierarchy of sustainable waste management, which includes avoidance, reduction, reuse, recycling, and final disposal. Furthermore, Islamic values regarding cleanliness and the avoidance of wastefulness provide moral legitimacy for waste management policies. This article also presents a table integrating fiqh al-bī’ah values with waste management actions and proposes a conceptual model that can be adapted by local governments, communities, and educational institutions. The implementation of this model is expected to strengthen ecological awareness among Muslims and improve the effectiveness of Indonesia's waste management policies